2009
DOI: 10.1007/s10726-008-9151-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Emotion and Language in Dyadic E-negotiations

Abstract: This paper examines the emotion and tone of language used by e-negotiation participants. Eight hundred e-negotiations of varying lengths were studied and significant differences between successful and unsuccessful e-negotiations were uncovered. Participants in successful e-negotiations expressed significantly more positive emotion and agreeable language, and significantly less negative language in their textual exchanges than participants in failed e-negotiations. Further, successful e-negotiations were shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Data from social media is recently used in models of the formation of opinions (see, e.g., Sobkowicza et al, 2012). It also been shown that emotions do play a role in model based e-negotiations (Hine et al, 2009) The natural next step is to use agent based models to simulate and direct peoples' opinions. An example is the work by Mosler and Martens (2008) on changing environmental attitudes by agent-based simulators.…”
Section: Communicationmentioning
confidence: 99%
“…Data from social media is recently used in models of the formation of opinions (see, e.g., Sobkowicza et al, 2012). It also been shown that emotions do play a role in model based e-negotiations (Hine et al, 2009) The natural next step is to use agent based models to simulate and direct peoples' opinions. An example is the work by Mosler and Martens (2008) on changing environmental attitudes by agent-based simulators.…”
Section: Communicationmentioning
confidence: 99%
“…Operational since 1995, Inspire has been used extensively for teaching and research (e.g., Hine et al 2009;Kersten and Zhang 2003). Participants are recruited from negotiation courses for university students and practitioners.…”
Section: Data and Sample Descriptionmentioning
confidence: 99%
“…making demands, threatening actions), or can appear so in the way that they are delivered. In a study of evocative language in negotiations, Hine et al (2009) found that there was proportionately more agreeable language (e.g. words like "alright," "fine," "indeed") and less negative language (e.g.…”
Section: H1mentioning
confidence: 99%